Features of geospatial organization of retail trade services in rural areas - Дудник, І. М. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
Formulation the problem. The service sector serves as an important component of the economy of any state, region. It became to develop especially rapidly for the last decades due to formation post-industrial society. The service sector plays a significant role in vital activity of society since it provides the population employment, satisfy population’s need in services, and ensures filling the local budgets. One of the most dynamic branches of the service sector is retail trade. There are significant transformations of this sector in rural areas, its territorial organization, but there is a lack of human-geographical research on the mentioned topic. The aim of the article is consideration the human-geographical approach to the study of service sector and retail trade in rural areas in particular. Research results. The author has analyzed the concept of "territorial systems of services as a set of direct and indirect interconnected enterprises. Territorial systems of services are components of the socio-geographical system. There are direct (links between enterprises in one branch) and indirect (links to the common use of territory, industrial, transport infrastructure, flows of people to satisfying needs, administrative and managerial, economic links) links within the territorial system of services. The specialized territorial system of services (a set of interconnected enterprises in one branch) is highlighted, which is a part of the integrated territorial system of services, it has bodies of sectorial and sectorial-territorial management, it is characterized by incomplete completeness, the specialized territorial system of services is found in its “pure form” very rarely, it is distinguished by a noticeable internal differentiation. Productive, managerial, and competing links plays significantly in formation the specialized territorial systems of services. The following indicators are used for the study of the territorial system of services: provision of commodity mass, provision of retail space, provision of staff, territorial concentration of trade objects, average radius of the service area of the center (enterprise). The technique of the analysis territorial differentiation of indicators involves the study the content of the territorial development of a chosen process (phenomena), choice of indicators, delimitation the study area, statistical ordering of indicators, construction the cartographic models, identification spatial dependencies, trends, prospects development.